Employee Engagement and Performance: The Role of Religious-Centric Organizational Commitment in Islamic Private Higher Education Institutions, Indonesia - Syahrial, Hery; Ramadhan, Muhammad; Sudiarti, Sri (LPPM, Universitas Islam Syarifuddin Lumajang, 2025)
This study aims to examine the role of RCOC in the relationship between EE and EP by exploring direct and indirect effects. Data from lecturers of Islamic private universities in North Sumatra Province were collected through surveys to explore EP. Hypotheses were tested using SEM with the application AMOS with a sample of 200 respondents. The results showed that RCOC has not been able to play a significant role in bridging the relationship between EE and EP. This study contributes: First, to the author's knowledge, this study is the first empirical study regarding the role of RCOC in bridging the relationship between EE and EP. Second, it enriches the literature on SIT by demonstrating the relationships between EE, RCOC and EP, particularly in higher education. This study also enriches the organizational behavior literature by using a few mediating variables to improve the relationship between employee engagement and employee performance on the context of Islamic higher education in Indonesia.